Analysis of a terminal Xp22.3 deletion in a patient with six monogenic disorders: implications for the mapping of X linked ocular albinism. Issue 10 (October 1993) - Meindl, A; Hosenfeld, D; Brückl, W; Schuffenhauer, S; Jenderny, J; Bacskulin, A; Oppermann, H C; Swensson, O; Bouloux, P; Meitinger, T
Abstract : The molecular characterisation of chromosomal aberrations in Xp22.3 has established the map position of several genes with mutations resulting in diverse phenotypes such as short stature (SS), chondrodysplasia punctata (CDPX), mental retardation (MRX), ichthyosis (XLI), and Kallmann syndrome (KAL). We describe the clinical symptoms of a patient with a complex syndrome compatible with all these conditions plus ocular albinism (OA1). He has a terminal Xp deletion of at least 10 Mb of DNA. Both the mother and sister of the patient are carriers of the deletion and show a number of traits seen in Turner's syndrome. The diagnosis of ocular albinism was confirmed in the patient and his mother, who shows iris translucency, patches and streaks of hypopigmentation in the fundus, and macromelanosomes in epidermal melanocytes. By comparative deletion mapping we can define a deletion interval, which locates the OA1 gene proximal to DXS143 and distal to DXS85, with the breakpoints providing valuable starting points for cloning strategies.